Real-Time Video Filtering Using Python: A Study on Dynamic Video Enhancement Techniques - Ramadhan, Fahri; Stirman, Aini Nur Rachimah; Dharmawan, Fauzan; Astharini, Dwi (EXSACT-A, 2024)
Abstract—This paper presents a basic exploration of digital image processing method in representing a color spectrum using Python. Digital Image Processing is a science that moves to create, analyze, and produce information in the form of images with various coloring. The filters used in this paper are Red and Black Frame, Edge Detection, Negative and HSV in Python. The results of this filter show the difference in the resulting color spectrum. By separating the color spectrum, you will get a color output that varies according to the command.Keywords— Image Processing, Filter, Intensity, Color Spectrum.